2014
DOI: 10.1002/ejhf.196
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of spironolactone against anthracycline‐induced cardiomyopathy

Abstract: Aims The protective effect of beta‐blockers, ACE inhibitors, and ARBs on anthracycline cardiotoxicity has already been demonstrated, but the effect of aldosterone antagonism, which inhibits the last step of the renin–angiotensin–aldosterone system (RAAS), was questioned. This study sought to investigate whether spironolactone protects the heart against anthracycline‐induced cardiotoxicity. Methods and results Eighty‐three female patients who were diagnosed with breast cancer were included in the study. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
135
1
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(147 citation statements)
references
References 27 publications
1
135
1
10
Order By: Relevance
“…76 Finally, a study has recently reported the preventive effects of spironolactone on anthracycline-induced myocardial toxicity in patients with breast cancer. 77 Important limitations of all of these studies [67][68][69][70][71][72][73][74][75][76][77][78] include the small number of patients treated, differences in study design, varying malignancies being studied and chemotherapy regimens used, and short follow-up times. In addition, in most studies, the mortality rate was lower than expected, and the reported beneficial effects on the incidence of HF and LVEF decline did not translate to lower mortality ( Table 2).…”
Section: Administration Of Cardioprotective Drugsmentioning
confidence: 99%
“…76 Finally, a study has recently reported the preventive effects of spironolactone on anthracycline-induced myocardial toxicity in patients with breast cancer. 77 Important limitations of all of these studies [67][68][69][70][71][72][73][74][75][76][77][78] include the small number of patients treated, differences in study design, varying malignancies being studied and chemotherapy regimens used, and short follow-up times. In addition, in most studies, the mortality rate was lower than expected, and the reported beneficial effects on the incidence of HF and LVEF decline did not translate to lower mortality ( Table 2).…”
Section: Administration Of Cardioprotective Drugsmentioning
confidence: 99%
“…110 In a recent study of 83 breast cancer patients, 25mg of spironolactone daily during anthracycline treatment mitigated a decrease in LVEF. 111 Lastly, statins have shown benefit for the prevention of anthracycline-based cardiotoxicity in a small single center study. 112 In the breast cancer literature, continuous statin use has been shown to decrease incident heart failure hospitalization among those receiving anthracyclines.…”
Section: Strategies To Improve Autonomic Functionmentioning
confidence: 99%
“…Small randomized controlled trials have evaluated the utility of using mainstays of heart failure therapy, renin angiotensin inhibitors, aldosterone inhibitors and beta-blockers, as preventive therapy for chemotherapy-related cardiotoxicity (31, 6671). None of these studies looked solely at older patients, but neither were they excluded.…”
Section: Medicationsmentioning
confidence: 99%
“…In the MANTICORE 101-Breast trial, perindopril and bisoprolol each attenuated trastuzumab-related declines in left ventricular systolic function, but did not prevent concurrent left ventricular remodeling, which was the primary outcome measure (73). In a double-blind, placebo-controlled study of spironolactone given simultaneously with anthracycline therapy, spironolactone had a protective effect in the development of left ventricular systolic dysfunction (71). Despite the favorable evidence presented above, routine prophylactic use of these therapies for cardiotoxicity is limited by the lack of consensus, as noted in two meta-analysis with differing conclusions on the benefits of these preventive strategies (32, 74).…”
Section: Medicationsmentioning
confidence: 99%